Obstáculos al desarrollo de las pequeñas medianas empresas en América Latina - Zevallos V., Emilio (2006)
This document reports progress made in compared research about the environment, barriers and prospects facing small and intermediate size companies in eight Latin American countries, although only six are presented in this paper, namely Argentina, Colombia, Costa Rica, Chile, El Salvador and Panama. The first section briefly presents each country’s business environment in terms of prevailing concepts, the overall business universe and its trouble spots. It also aims at establishing a general typology of companies. The second section reviews the study’s methodology while the third chapter deals with the elements for doing business in each country (this paper deals only with the financing, human resources and technology components). Finally, it presents some reflections about the condition of small and intermediate companies and some guidelines for public policy actions.